Finding the true prevalence of obstructive lung disease: two steps forward and one step back. Issue 6 (18th June 2020) - Russell, Richard E.K.; Wang, Kay
We are writing this editorial at a time when many of the readers of this journal are living through the coronavirus disease 2019 (COVID-19) crisis. At the moment, the world is locked down. The most urgent question that medicine is trying to answer is: what is the prevalence of COVID-19 infection in any given population? The answer to this question will enable epidemiologists, economists and politicians to make an informed decision about ending the social and physical isolation measures currently in place. This information is critical and essential, not only in this time of COVID-19 but also to allow us to manage any disease. True prevalence is one of the holy grails of long-term condition management, especially for COPD and asthma [1]. Getting a true measure of disease prevalence is difficult but fundamental to medicine. The process itself is valuable, but the results have to be reviewed in the context of the healthcare system and country they were collected in. https://bit.ly/2ThxaxF